Gender and the CMO: do the differences make a difference?. (19th May 2021) - Pitt, Christine
ABSTRACT: Despite efforts to address the lack of female representation in executive leadership roles, the number of women in leadership roles is still low in comparison to men. Data in the form of online interviews were collected for a sample of 69 CMOs from the World's Most Influential CMO's report by Forbes Magazine and analyzed using the automated text analysis software, LIWC, employing the dimensions of Analytic, Clout, Authentic, and Tone. A series of ANOVAs was conducted to determine the impact of gender on these dimensions. Clout and Authentic were significantly impacted by the gender of the CMO. The paper considers two gender communication theories that could potentially explain these differences. The paper concludes by discussing managerial implications, acknowledging the limitations, and identifying avenues for future research.